A bioeconomic perspective on the Norwegian Barents Sea cod fishery - Eide, Arne (Universitetet i Tromsø, 2008)
This is a Dr. philos. thesis. Papers number 1, 2, 4 and 7 of the thesis are not available in Munin: 1. Arne Eide, Frode Skjold, Frank Olsen and Ola Flaaten: 'Harvest Functions: The Norwegian Bottom Trawl Cod Fisheries', Marine Resource Economics, Volume 18, pp. 81–93 (MRE Foundation - publisher's restrictions). Available at http://purl.umn.edu/28294 2. Arne Eide and Knut Heen: 'Economic impacts of global warming. A study of the fishing industry in North Norway', Fisheries Research 56 (2002) 261–274 (Elsevier - publisher's restrictions). Available at http://dx.doi.org/10.1016/S0165-7836(01)00324-1 4. Arne Eide: 'An integrated study of economic effects of and vulnerabilities to global warming on the Barents Sea cod fisheries', Climatic Change (2008) 87:251–262 (Springer - publisher's restrictions). Available at http://dx.doi.org/10.1007/s10584-007-9338-0 7. Arne Eide & Arild Wikan: 'An Analysis of a Nonlinear Stage-Structured Cannibalism Model with Application to the Northeast Arctic Cod Stock', Bulletin of Mathematical Biology (2004) 66, 1685–1704 (Elsevier - publisher's restrictions). Available at http://dx.doi.org/10.1016/j.bulm.2004.03.005